Differential Information and Dynamic Behavior of Stock Trading Volume - He, Hua; Wang, Jiang (Review of Financial Studies, 1995)
This article develops a multiperiod rational expectations model of stock trading in which investors have differential information concerning the underlying value of the stock. Investors trade competitively in the stock market based on their private information and the information revealed by the market-clearing prices, as well as other public news. We examine how trading volume is related to the information flow in the market and how investors' trading reveals their private information.